2016
DOI: 10.1007/s13224-016-0931-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical and Laparoscopic Features of Endometriosis Among Infertile Women

Abstract: More than 50 % of patients in our study were asymptomatic; however, the presence of menorrhagia, dysmenorrhoea, dyspareunia and chronic pelvic pain are also clinically statistically significant. So, we would like to recommend the evaluation and treatment of a patient reporting in gynaecological OPD with the above-mentioned complaints with high suspicion of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
12
2
Order By: Relevance
“…This rate is higher than the previously reported rates of 4.4% and 1.4% found among women undergoing laparoscopic evaluation for tubal factor infertility in Nigeria. However, the present rate was much lower than the rate of 54.9% reported among infertile women in India …”
Section: Discussioncontrasting
confidence: 80%
“…This rate is higher than the previously reported rates of 4.4% and 1.4% found among women undergoing laparoscopic evaluation for tubal factor infertility in Nigeria. However, the present rate was much lower than the rate of 54.9% reported among infertile women in India …”
Section: Discussioncontrasting
confidence: 80%
“…[1][2][3][4] The main symptoms are chronic pelvic pain and infertility. Some large-scale studies showed a prevalence of endometriosis in 25% to 40% of infertile women, 5,6 as well as low basal ovarian reserve, low fertility rate, and embryo cleavage. 7 In addition, the pro-inflammatory and angiogenic factors in the ectopic endometrium may contribute to abnormal placentation 2,8 and to develop major obstetrical complications including activation of the mechanisms involved in preterm birth (PB) 1,2,9 ; newborns of these women need more frequent neonatal intensive care unit admissions.…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis was staged during surgical visualization according to the revised American Fertility Society (rAFS) [85] or revised American Society for Reproductive Medicine (rASRM) [86] and was reported in 26 studies (Supplemental Table 1). A total of 19 studies provided staging details based on the rAFS system [32,37,39,49,50,52,54,56,[58][59][60][61][62][63]70,72,76,81,83], and 7 studies were staged by the rASRM [26,29,34,38,40,64,67] system. A total of 20 studies (77%) were either based in a single hospital or clinic or used data from a hospital or insurance system.…”
Section: Endometriosis Stage At Diagnosismentioning
confidence: 99%